Contra C*-Continuity in Topological Spaces - P.Chandramoorthi (International Journal of Engineering and Management Research, 2019)
In this paper, we introduce the notions of contra C*-continuity and contra C(S)-continuity in topological spaces and study the relations of contra C*-continuity with various generalized contra continuity maps.